Unique Superparamagnetic‐like Behavior Observed in Non‐π‐delocalized Nitroxide Diradical Compounds Showing Discotic Liquid Crystalline Phase. Issue 65 (31st October 2018) - Takemoto, Yusa; Zaytseva, Elena; Suzuki, Katsuaki; Yoshioka, Naoki; Takanishi, Yoichi; Funahashi, Masahiro; Uchida, Yoshiaki; Akita, Takuya; Park, Jayeong; Sato, Shuichi; Clevers, Simon; Coquerel, Gérard; et al.
Abstract: A unique superparamagnetic‐like behavior and a large "positive magneto‐LC effect" were observed in the solid phases and the hexagonal columnar (Colh ) liquid crystalline (LC) phase, respectively, of novel achiral non‐π‐delocalized nitroxide diradical compounds ( R, S )‐1, which showed polymorphism in the solid phases (solids I and II). The SQUID magnetization measurement revealed that (1) ( R, S )‐1 containing a small amount of racemic diastereomers ( R *, R *)‐1 possessed an unusual and large temperature‐independent magnetic susceptibility ( χ TIM >0) component in the original nanocrystalline solid I that was responsible for the observed superparamagnetic‐like behavior under low magnetic fields and did not arise from the contamination by extrinsic magnetic metal or metal ion impurities, besides ordinary temperature‐dependent paramagnetic susceptibility ( χ para >0) and temperature‐independent diamagnetic susceptibility ( χ dia <0) components, (2) a large increase in molar magnetic susceptibility ( χ M ) (positive magneto‐LC effect) that occurred at the solid I‐to‐liquid crystal transition upon heating was preserved as an additional χ TIM increase in the resulting polymorphic nanocrystalline solid II by cooling, and (3) such unique magnetic phenomena were induced by thermal processing for ( R, S )‐1 or by adding a small amount of ( R *, R *)‐1 to ( R, S )‐1 as the impurity. Abstract : Magnetic and mesomorphic : Novel achiral non‐π‐delocalized nitroxide diradical compounds that showed a unique superparamagnetic‐like behavior in the nanocrystalline and columnar hexagonal liquid crystalline phases were prepared and characterized.